Strategi Guru pada Era Digital dalam Membina Karakter Sopan Santun Siswa Kelas V di SDN 115 Pekanbaru - Paluvi, Indriyani; Nukman, Muhamad (Cetta: Jurnal Ilmu Pendidikan, 2025)
The development of the digital era has significantly influenced students' attitudes and character, particularly in relation to politeness. This study aims to describe the strategies implemented by teachers to foster the character of politeness among Grade V students in the digital era at SDN 115 Pekanbaru. Using a qualitative approach, data were collected through observations, interviews, and documentation involving teachers, principals, students, and parents. The findings reveal that teachers employ several strategies, including serving as behavioral role models, establishing effective communication, enforcing rules, strengthening character education, and engaging parents and the broader school environment. Challenges encountered include exposure to inappropriate digital content, limited parental supervision, and time constraints for teachers. To address these issues, teachers enhance character development through extracurricular activities and consistent positive reinforcement. In conclusion, the strategies applied by teachers effectively support the development of students’ politeness character, especially when supported by collaboration among schools, families, and the surrounding community.